2014
DOI: 10.1039/c4py00631c
|View full text |Cite
|
Sign up to set email alerts
|

Schiff based injectable hydrogel for in situ pH-triggered delivery of doxorubicin for breast tumor treatment

Abstract: In this study, we report a facile approach to develop an injectable hydrogel with an in situ and pH sensitive drug delivery system for cancer treatment. The hydrogel was based on modified chitosan and alginate. We conjugated doxorubicin (DOX) to succinated chitosan (S-chi) via a Schiff base between a ketone group in the DOX and an amine group in the S-chi, which led to a pH sensitive release of DOX upon the stimulus of an acidic tumor microenvironment. Hydrogel formed in minutes while DOX conjugated S-chi was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
68
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 103 publications
(69 citation statements)
references
References 56 publications
0
68
0
1
Order By: Relevance
“…For example, the obvious difference in pH between normal tissues (pH ∼ 7.4) and acidic tumor tissues (pH < 6.8) has motivated researchers to design pH-responsive polymeric prodrugs via acid-labile covalent linkages like benzoicimine bond, 39 Schiff's base bond, 40 and hydrazone bond 41 for tumor targeted delivery. Kataoka et al 42 have reported a pH-sensitive polymeric prodrugs by which doxorubicin (DOX) was conjugated to the poly(ethylene glycol)-b-poly(β-benzyl-L-aspartate) through acid-sensitive hydrazone linkages, which showed a highly sensitive drug release under an acidic microenvironment.…”
mentioning
confidence: 99%
“…For example, the obvious difference in pH between normal tissues (pH ∼ 7.4) and acidic tumor tissues (pH < 6.8) has motivated researchers to design pH-responsive polymeric prodrugs via acid-labile covalent linkages like benzoicimine bond, 39 Schiff's base bond, 40 and hydrazone bond 41 for tumor targeted delivery. Kataoka et al 42 have reported a pH-sensitive polymeric prodrugs by which doxorubicin (DOX) was conjugated to the poly(ethylene glycol)-b-poly(β-benzyl-L-aspartate) through acid-sensitive hydrazone linkages, which showed a highly sensitive drug release under an acidic microenvironment.…”
mentioning
confidence: 99%
“…In this work, a polysaccharide hydrogel was synthetized via Schiff base reaction between carboxymethyl chitosan (CMCTS) and glucan. In addition, Schiff base itself has antibacterial, sterilization, antitumor, and antiviral bioactive . Water‐insoluble VCZ was loaded through the inclusion into the β‐cyclodextrin (β‐CD) cavity on the linear poly β‐CD chain, which was in situ twined in the cross‐linked structure formed by polyaldehyde dextran (PAD) and CMCTS in the physiological solution .…”
Section: Introductionmentioning
confidence: 99%
“…These scaffolds play the role of the extracellular matrix (ECM) to organize cells into a 3D structure and to deliver stimuli, which regulate the tissue's growth and generation. 11 Polymers derived from natural materials such as collagen, HA, chitosan and alginate are frequently used in tissue engineering, because they have low toxicity and similar macromolecular components to the natural ECM. 10 Because of the similar architecture to the ECM of many tissues, they can help to promote cell proliferation and cell function.…”
Section: Introductionmentioning
confidence: 99%